The Art of Public Speaking : student CD-ROM Version 4.0 - Stephen E. Lucas (The McGraw-Hill Companies, 2004)
Disk 1 berisi : Videos : Video clips, full student speeches. Study Aids : study questions, qutline exercises, key term flashcard. Tools : speech qutliner, speech checklist, notepad. Reference Aids : Bibliography formats, key terms. Disk 2 berisi : Full student speeches yg berisi 18 video klips.